2019
DOI: 10.1097/corr.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Association Between Articular Cartilage Damage and Subsequent THA 20 Years After Hip Arthroscopy for Labral Tears?

Abstract: Background Few studies have examined long-term outcomes for patients after arthroscopic treatment for intraarticular hip conditions, and none have done so beyond 10 years postarthroscopy. Examining outcomes beyond 10 years is necessary to determine factors that contribute to conversion to THA in patients undergoing hip arthroscopy for labrochondral damage. Questions/purposes (1) What is hip survivorship free from THA in patients who underwent arthroscopic labral débridement, with or without chondroplasty at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…This would suggest that in the absence of OA, age may be less of a factor than was previously thought. Dwyer et al 9 suggested that the presence of articular cartilage damage was a more potent indicator of THR conversion than was age, with comparable survivorship rates observed in patients with similar cartilage damage, irrespective of age. Similarly, in the current study, an Outerbridge grade 4 on the femoral head was predictive of subsequent THR in regression analysis, whereas age and any other patient factors were not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would suggest that in the absence of OA, age may be less of a factor than was previously thought. Dwyer et al 9 suggested that the presence of articular cartilage damage was a more potent indicator of THR conversion than was age, with comparable survivorship rates observed in patients with similar cartilage damage, irrespective of age. Similarly, in the current study, an Outerbridge grade 4 on the femoral head was predictive of subsequent THR in regression analysis, whereas age and any other patient factors were not.…”
Section: Discussionmentioning
confidence: 99%
“…Sex (Table 5) was not associated with THR (P = .687) or RHA (P = .659), and there were no differences between sexes and PROMs with the exception of the UCLA score. Males had significantly higher UCLA scores at baseline compared with females (median [IQR], 9 [6][7][8][9][10] vs [4][5][6][7][8][9], respectively; P = .001; ES = 0.363 [medium]), which was maintained at 10 years (median [IQR], 9 [7][8][9][10] vs [6][7][8], respectively; P = .001; ES = 0.382 [medium]).…”
Section: Effects Of Sexmentioning
confidence: 99%
“…Other studies have also shown that prior hip arthroscopy or surgeries have been associated with predictors of clinical outcomes, 14 , 31 whereas the present study did not note prior hip arthroscopy as a significant predictor of conversion, despite it being statistically significant. Additional factors previously associated with conversion have been worsening preoperative evidence of arthritic changes or chondral damage 20 , 22 , 23 , 25 , 26 , 28 , 33 , 34 , 35 or acetabular morphology. 36 Contralateral THA has also been associated with increased conversion to THA after hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Poorer outcomes have been associated with older age at the time of hip arthroscopic surgery. 18 Frank et al 21 reported that patients older than 45 years performed worse compared with younger patients. Nevertheless, the authors stated that physiological age instead of chronological age alone may be more representative of the durability of the hip joint, which is a concept that we share.…”
Section: Discussionmentioning
confidence: 99%